Perlindungan Hukum dalam Ulasan Konsumen di Media Sosial - Fanny Natalie, Elizabeth; Ferry Rosando, Abraham (Jurnal Syntax Fusion, 2023)
Currently there are many social media users in the digital economy era, due to the easy and fast dissemination of information that can be received by users. Apart from being aimed at finding information, in fact social media is also used by businesses to interact with consumers in all corners of the region. With the convenience of consumers in using and making transactions on social media, there are lots of positive and negative values that are obtained by business people. The assessment obtained by business actors is in the form of reviews on products or services that are sold and enjoyed by consumers. However, this assessment has a positive or negative impact on business actors and society. The purpose of conducting this research is to analyze that ratings or reviews are tools or media used by consumers to convey criticism, suggestions or opinions on a product or service on social media and how consumers' mechanisms in providing limits on reviews or reviews of products or services are used so that the reviews or comments made do not violate the law and consumers get legal protection. In this study using normative legal research. The results of this study indicate that reviews or reviews given by consumers are the right media to convey all forms of opinion and also criticism of suggestions for the use of products and services provided by businessmen. With the media in the form of this review, consumers can provide an assessment by taking into account the applicable norms and laws, so that they continue to respect the rights of others.